Reanimation of Zombie Virus : Facts and Fiction - Kanti Biswas, Sanjoy (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
The ancient amoeba virus unearthed by researchers and scientists have revived from the melted ice is ominously being called a”Zombie Virus”. The term "Zombie Virus" refers to viruses that have remained dormant for extended periods, raising concerns among scientists about their potential to cause severe diseases. The recent discovery of a "Zombie Virus in Russian ice" might seem like a plot from a horror movie, but the context of a post-pandemic world makes it less surprising. Researchers have successfully revived viruses that have been inactive for tens of millions of years, found in the Siberian permafrost Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 1-3